Two New Plant Records to Southern India - Balachandran, N.; Ravikumar, K.; Dhatchanamoorthy, N. (Indian Forester, 2016)
During the medicinal plant survey tour to Kalakkadu-Mundanthurai Tiger Reserve, Tamil Nadu two species viz. Gouania napalensisÂ Wall. of Rhamnaceae and Psychotria symplocifolia Kurz of Rubiaceae are collected which forms new report to southern India.